Valuing Information In An Information Age: The Price Model And The Emerging Information Divide Among Individuals, Societies, And Nations - Maina, Charles (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The problem of valuing and pricing information continues to exist despite years of research on the topic. Previous research on the various ways that consumers value information and on how price has been previously applied as a system for valuing information is examined. The paper examines whether price contributes to the emerging information divide and to identify existing gaps. . .